Structural evaluation and antimicrobial activity of analog peptides from stigmurin - Parente, Adriana Marina e Silva (2022)
Antimicrobial peptides are molecules considered one of the first defense lines against microorganisms. From the transcriptome of a scorpion venom gland, our research group identified the antimicrobial peptide Stigmurin, from which amino acid residues were changed and two analog peptides denominated StigA6 and StigA16 were designed and studied. These peptides presented in vitro activity against Gram-positive and Gram-negative bacteria higher than the native peptide. To deepen the knowledge on these peptides here we studied their antibacterial activity against multidrug-resistant bacteria in vitro and in vivo assays of larval infection and mice polymicrobial sepsis. The structures of these peptides were evaluated when interacting with lipid vesicles by circular dichroism and by liquid-state nuclear magnetic resonance (NMR). Regarding their in vitro antibacterial activity, StigA6 and StigA16 showed high activity against multidrug-resistant S. aureus and P. aeruginosa, and antibiofilm effect on multidrug-resistant S. aureus. Both peptides were able to control infections in Galleria mellonella larvae, increasing survival and reducing colony-forming units, hemocytes and melanization. In mice polymicrobial sepsis, the analog peptides were able to reduce viable microorganisms, leukocytes migration and myeloperoxidase activity. As for their interaction with lipid vesicles both peptides showed higher interaction with bacterial membrane-mimetic vesicles than with eukaryotic membrane-mimetic vesicles. NMR data showed that both analog peptides presented high amphipathicity and longer helical structure than the native peptide, Stigmurin, suggesting that lysine placement is important to helix determination. Therefore, these peptides are interesting targets in the study of new anti-infective molecules.